Emotional and spiritual intelligence impacts on entrepreneurial intention: Serial mediation of creativity and proactive attitude - Radiman, Radiman; Sukiman, Sukiman; Agus, Rizal (Asian Management and Business Review, 2024)
This study investigates the relationship between emotional and spiritual intelligence from an Islamic perspective, with creativity and proactive attitude as mediating variables. The research utilized a survey among students at several private Islamic universities in Medan City. These universities were selected due to their Islamic vision and the presence of central business incubators or entrepreneurship centers. Students who carried out entrepreneurial activities from semester 3 to semester 7, totaling 120 people, were selected as sample size sufficiently representative of the population using a simple random sampling method. Data analysis was performed using Structural Equation Modelling (SEM) from the statistical software package LISREL 8.80. The results showed that all the hypotheses tested in this study were supported, meaning that the Islamic perspective on emotional and spiritual intelligence was proven to encourage entrepreneurial intentions at Islamic universities in Medan City with creativity and proactive attitude as a serial mediator. Creativity and proactive attitudes mediate the relationship between emotional and spiritual intelligence towards entrepreneurial intention. Creativity and proactive attitudes reinforce the relationship between emotional and spiritual intelligence toward entrepreneurial intention. The better the creativity and proactive attitudes of the respondents, the stronger the relationship between emotional and spiritual intelligence towards entrepreneurial intention.